Towards a Mobilist Tectonic Model for Part of the Archean of Northwestern Ontario - Blackburn, C. (Geoscience Canada, 1980)
Summary Models that have been proposed forevolution of the Archean crust can beconsidered as either fixist, involvingprocesses acting in place such as riftingand diapirism, or mobilist. involving horiz-ontal processes such as lithospheric platemovements, of which rifting and diapirismare adjuncts. Consideration of regional geology of aportion of Superior Province suggests thatsupracrustal sequences can be tracedacross subprovince boundaries, but thatthe boundaries have been subsequentlymodified by considerable faulting bothdip-slip and strike-slip. Within the Wabi-goon Subprovince lowermost supracrus-tal sequences are everywhere of thicktholeiitic mafic volcanics that show noevidence of being ensialic. Granite diapirism accounts for muchbut not all deformation of supracrustalsequences. Crustal shortening independ-ent of diapirism is indicated by the style ofthrust faulting. Geochronology supportsthe concept that batholithic invasion wascoeval with calc-al kali ne voieanism, andpaleomagnetism confirmsthat cratoniza-tion was complete by about 2.6 Ga ago. Fixist models do not fully explain theseobservations, whereas a mobilist model,because of its broader nature, can accom-modatethem all.